CARACTERIZACION ESTRUCTURAL DE LOS ENCINARES DE CATALUÑA Marc (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
In this paper, a characterization of structure of holm-oak forests in the Northeastem Iberian Peninsula is proposed. The study is based on different features of these forests, both at the stand and at the individuallevel.